Identification of fungi in white cachama (Piaractus brachypomus) in semi-intensive crops of Norte de Santander, Colombia (Orinoquia, 2014)
In the study of fish pathology, fungi are one of the infectious agents that can cause serious health problems and even triggering processes of morbidity and mortality in fish stations. This results in large economic losses for the sector. Literature on fish diseases reported that fungi prevalent in Colombia as an actor in high incidence in fish. The objective of this research was establishing the presence of fungi in cachama spp. by microbiological isolation in semi-intensive production of Norte de Santander - Colombia. They were studied in semi-intensive fish belonging to eleven municipalities of Norte de Santander. It was collected forty-two fishes with clinical symptoms compatible with mycoses, of which samples were taken and were seeded into agar peptone enriched with glucose, malt and Saboroud, the cultures were incubated at 25° C and 37° C for 24 to 36 hours after this time were made descriptions. Were isolated from the samples observed four genera of fungi (Fusarium sp, Mucor sp, Penicillium sp and Aspergillus sp.) and two yeasts groups classified in Ascomycetes, Zygomycetes and two Cándidas, determining a ratio of Ascomycetes 50% Yeasts and 25% Zygomycetes, 25%. Most of these fungi are opportunistic and are found in all environments in both plants and animals (fish). Fungal isolates of Fusarium, Aspergillus, Penicillium and Mucor can be pathogenic in both animals and humans. This information allows us to build a database and a epidemiological map on white cachama fungal diseases in Norte de Santander, Colombia.
Keywords: fishes; fungi; health; isolation